CORRELATION BETWEEN WAIST-HIP RATIO AND WAIST CIRCUMFERENCE AS A PREDICTOR PARAMETER IN FRAMINGHAM RISK SCORE FOR HARD CORONARY HEART DISEASE AND KIDNEY FUNCTION (CARDIO-RENAL SYNDROME) - Teguh, Stanislas; Priyana, Andria; Kartika, Ronald; Firmansyah, Yohanes; Santoso, Alexander (Lembaga Penelitian Dan Pengabdian Kepada Masyarakat Universitas Wijaya Kusuma Surabaya, 2025)
Cardio-renal syndrome reflects the intricate link between heart and kidney health, where the dysfunction of one organ worsens the other. In coronary heart disease, the Framingham Risk Score (FRS) is a key tool for estimating the 10-year risk of myocardial infarction (MI) or death. Abdominal obesity, often measured by waist-hip ratio (WHR), has emerged as an important cardiovascular risk factor, potentially enhancing existing predictive models. This study aimed to evaluate the correlation between FRS for Hard Coronary Heart Disease and kidney function (Cardio-Renal Syndrome) and to assess WHR as a predictive parameter for FRS. This study conduct a cross-sectional study among 52 employees of Yayasan Kalam Kudus, it analyzed the correlation between FRS (